ECONOMIC PROBLEMS OF SMALL ENTREPRENEURSHIP IN ACCELERATING OF SCIENTIFIC AND INNOVATIVE ACTIVITIES - E. P. Davidyuk; S. F. Davidyuk (Дискурс)
The paper contents the analysis results of Russian small and medium business in the innovation area. The data of the first and last official statistical surveys of the Rosstat (2003 and 2015) were used in the article, OECD comparative publications and the forecasts of the governmental structures. The economic problems of state financing, taxation and administrative regulation are discussed.